Does the Chilean TURFs achieve the sustainability of its fisheries? Evaluation of its performance considering the administrative, biological, and economic dimensions of this fisheries regime - Romero, Pedro; Bularz, Bryan; Arenas-Proaño, Gabriela; Moreno, Daniel (Frontiers in Marine Science, 2025)
The management based on the allocation of Territorial Use Rights for Fisheries (TURF) is a mechanism used to achieve the sustainable development of the activity and its fisheries. In Chile, the measure began in the late 1990s, and after 30 years, it remains uncertain whether its implementation has achieved this goal. The objective of the present study is to evaluate the historical performance of the MEABR regime across biological, economic, and administrative dimensions. To achieve this, objectives for each dimension were defined in collaboration with the administrative professionals of the regime, leading to the identification of eight evaluation indicators. The performance results indicate that, in general, during the period from 1998 to 2020, the MEABR regime has met institutional objectives at an “acceptable” level in the biological, economic, and administrative dimensions. Specifically, regarding resource performance, it is observed that species such as loco, sea urchin, and the macroalgae kelps have seen increased initial densities within the areas; however, ecological conditions remain below acceptable levels, generating uncertainty about the future state of these resources. The study identifies the level of success of the regime and proposes strategies to reduce gaps to achieve sustainability objectives.